Tribal savage laws and its association with honour-based murders in Pakhtun society - Bangash, Arshad; Bangash, Arman Ullah Bangash; Bibi, Fariha Bibi (Journal of Peace, Development and Communication, 2022)
The study carried out with positivistic methodology in tribal District Kurram erstwhile known as Kurram Agency. An appropriate sample size i.e. 377 respondents (Maliks) were randomly selected and questionnaire was used as tool of data collection. The data was presented at univariate, bivariate and multivariate levels of analysis through frequencies/percentages distributions and Chi-Square test statistics. Study results concluded that Pakistani women suffered and ruined due to systematic discrimination and institutional failure. The institutional dynamics of tribal societies is supported by normative orders while the existing penal codes always encourage honour killing. In case of any breach in case of honour norms violation, both the offenders are ought to be killed on the spot with impunity. Formal legal institutional framework, though in existence, however disposition of justice with regards to any breach is always treated through the prevalent customary norms and practices. ‘Jirga’ is a traditional mechanics is operative in the area due to its quick disposition of justice, while government legal institutions had been failed to address the issue of honour killing. State as a controlling mechanics needs to intervene by extending its laws to tribal areas, special laws should be passed from the legislative bodies to protect self and dignity of women and establishment of speedy courts with representation from both gender at state level were forwarded some the policy recommendations.